THE EFFECTIVENESS OF REGIONAL GOVERNMENT EMPOWERMENT ON PHARMACEUTICAL WHOLESALER LICENSES ON THE BALI PROVINCE - Joniada, I Made Wisnu; Styawati, Ni Komang Arini; Arjaya, I Made (YURIS: Journal of Court and Justice, 2024)
Pharmaceutical wholesalers (PBF) that are already licensed by Indonesian government have complied with the pre-operational business standard requirements and during operations are required to comply with the standards of good drug distribution procedures. However, there have been some cases of PBFs that have been licensed infringing on their business licensing obligations. These infringements will affect the quality of drugs and/or drug substances which could endanger consumers. Based on this phenomenon, monitoring by regional governments is important in maintaining businesses’ compliance with business standards. The objectives of this research were to examine and analyze several factors affecting the effectiveness of regional government supervision of PBF licenses in Bali Province. The method used is empirical legal method. To address the issues within this research, the author utilizes a sociological approach, a legal regulation approach, and a conceptual approach.  Furthermore, this research indicated that Bali Provincial Health Office supervision is ineffective in assuring compliance in the fulfilling of requirements and obligations by businesses. These conditions have been affected through legal substantial factors, legal structure, and legal culture.